1997
DOI: 10.1063/1.366533
|View full text |Cite
|
Sign up to set email alerts
|

1/f noise in anisotropic and giant magnetoresistive elements

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Thermally excited changes in the magnetization directions of such magnetic domains result in magnetic fluctuations with a magnitude ensemble average that translates to an inverse dependency on frequency. The magnetic fluctuations are translated into resistance fluctuations via the dependence of the resistance on the angle of the magnetization (van de Veerdonk et al, 1997). Note that the magnetization 1/f noise is superimposed on the sensor resistance, whereas the other noise sources contribute directly to the sensor voltage.…”
Section: Optimization Of Signal-to-noise Ratiomentioning
confidence: 99%
“…Thermally excited changes in the magnetization directions of such magnetic domains result in magnetic fluctuations with a magnitude ensemble average that translates to an inverse dependency on frequency. The magnetic fluctuations are translated into resistance fluctuations via the dependence of the resistance on the angle of the magnetization (van de Veerdonk et al, 1997). Note that the magnetization 1/f noise is superimposed on the sensor resistance, whereas the other noise sources contribute directly to the sensor voltage.…”
Section: Optimization Of Signal-to-noise Ratiomentioning
confidence: 99%
“…Unfortunately, magnetoresistance sensors exhibit a considerable amount of 1/f noise [6], which is associated with domain wall motion. This is a problem for military applications since the targets move slowly.…”
Section: Introductionmentioning
confidence: 99%
“…Such fluctuations determine a fundamental noise limit for MR-based devices. 8,9 However, Reed et al measured 1/f noise in MTJ sensors and observed that low-frequency sensor noise is dominated by resistance fluctuations in the tunnel barrier, and that these resistance fluctuations are due to charge trapping in the barrier. 10 In order to clarify the physical origin and evaluate the noise level of 1/f noise in MTJ's, we conducted a systematic study of low-frequency noise in high-quality MTJ sensors under different magnetic environment, i.e., with and without a hard-axis bias field perpendicular to the magnetic easy axis of the sample.…”
mentioning
confidence: 97%